2012
DOI: 10.1177/1473871612468877
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the intelligence analysis process through a longitudinal field study: Implications for visual analytics

Abstract: While intelligence analysis has been a primary target domain for visual analytics system development, relatively little user and task analysis has been conducted within this area. Our research community's understanding of the work processes and practices of intelligence analysts is not deep enough to adequately address their needs. Without a better understanding of the analysts and their problems, we cannot build visual analytics systems that integrate well with their work processes and truly provide benefit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Kang and Stasko recently demonstrated the importance of externalizing an analyst's thought process, of which making annotations is a key aspect [21]. They observed that analysts continuously build a conceptual model in the sensemaking process and suggested visual representations can be leveraged to help analysts browse the history of previous discoveries in order to "connect, group, and organize concepts."…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang and Stasko recently demonstrated the importance of externalizing an analyst's thought process, of which making annotations is a key aspect [21]. They observed that analysts continuously build a conceptual model in the sensemaking process and suggested visual representations can be leveraged to help analysts browse the history of previous discoveries in order to "connect, group, and organize concepts."…”
Section: Related Workmentioning
confidence: 99%
“…Facilitating annotations is an important aspect of supporting the knowledge externalization process [10,20,21,24]. Yet, commercial exploratory data analysis systems and visualizations that support annotations still present user-authored comments as lists; in a linear and textual form.…”
Section: Introductionmentioning
confidence: 99%
“…There exist a number of taxonomies for information visualisation tasks, both abstract [57,90] and more concrete [7,8,11,168,280], but we are primarily interested in taxonomies generated for network data. Due to the relative lack of work in this area, we do not further isolate the discussion to only taxonomies of dynamic network data.…”
Section: Visualisation Task Taxonomiesmentioning
confidence: 99%
“…Public health intelligence research is: "the concepts, methods, practices, and apparatuses assembled to monitor and detect health events" (French & Mykhalovskiy, 2013). Indeed, there has not been much research on any kind of intelligence analysis during a crisis, not only a public health crisis (Hutchins, Pirolli, & Card, 2007;Kang & Stasko, 2014).…”
Section: Information Issuesmentioning
confidence: 99%
“…For example, there is strong body of research on coordination of multiple agencies in crisis response (Bharosa et al, 2010); but we also need more research for crisis management longitudinally and being able to map events and decisions from months or even years ago to the current day, for a long duration crisis. This also has applications into information systems design (Kang & Stasko, 2014) for intelligence analysis and coordination during a long duration crisis.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%